The Nexus between Crime Rates, Poverty, and Income Inequality: A Case Study of Indonesia - Lilik Sugiharti, - (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
This study examines whether income inequality and poverty are determinants of crime rates across 34 provinces in Indonesia. Three indicators of income inequality and four poverty measures are tested to examine whether the dimension and degree of unequal welfare distribution are linked to crime occurrences. We use panel data from 2010 to 2019 with the Generalized Method of Moments (GMM) approach. The findings indicate that higher income levels and wider income inequality are associated with higher crime rates. Our first indicator of income inequality, non-food expenditure, has a larger impact on crime rates than our second and third indicators, i.e., the gap in food expenditure and the Gini ratio. Poverty is also positively associated with crime. The wider the poverty gap (a measure of poverty) and the severity index, the higher the deprivation levels among the poor, which lead to more crime. The significant and positive effect of poverty on crime rates, and the positive nexus between crime, income, and inequality suggest that Indonesia will face a higher crime risk as the country becomes increasingly more affluent. In such a scenario, policymakers can leverage education and investment (domestic and foreign) to minimize the crime rate. The government could also strengthen crime prevention programs, crime settlement systems, and policing in Indonesia, and raise the budget for social assistance.